Economic Insecurity Increases Physical Pain. (April 2016) - Chou, Eileen Y.; Parmar, Bidhan L.; Galinsky, Adam D.
The past decade has seen a rise in both economic insecurity and frequency of physical pain. The current research reveals a causal connection between these two growing and consequential social trends. In five studies, we found that economic insecurity produced physical pain and reduced pain tolerance. In a sixth study, with data from 33, 720 geographically diverse households across the United States, economic insecurity predicted consumption of over-the-counter painkillers. The link between economic insecurity and physical pain emerged when people experienced the insecurity personally (unemployment), when they were in an insecure context (they were informed that their state had a relatively high level of unemployment), and when they contemplated past and future economic insecurity. Using both experimental-causal-chain and measurement-of-mediation approaches, we also established that the psychological experience of lacking control helped generate the causal link from economic insecurity to physical pain. Meta-analyses including all of our studies testing the link from economic insecurity to physical pain revealed that this link is reliable. Overall, the findings show that it physically hurts to be economically insecure.